Sialyl Tn-expressing bladder cancer cells induce a tolerogenic phenotype in innate and adaptive immune cells - Carrascal, Mylene A (2017)
This work was supported by the Portuguese Foundation for Science and Technology (FCT) - PTDC/SAU-MII/67561/2006 and Premio Santander Totta - UNL (Paula A. Videira), LPCC/Pfizer2011 (Mylene A. Carrascal), SFRH/BPD/21619/2005 (M. Guadalupe Cabral), SFRH/BD/81860/2011 (Mariana Silva), SFRH/BD/45120/2008 (Paulo F. Severino) and SFRH/BPD/ 66288/2009 (Jose Alexandre Ferreira). FCT is co-financed by European Social Fund (ESF) under Human Potential Operation Programme (POPH) from National Strategic Reference Framework (NSRF).) and European Union, QREN, FEDER, COMPETE, for funding the Organic Chemistry Research Unit (QOPNA) (project PEst-C/QUI/UI0062/2013; FCOMP-01-0124-FEDER-037296).